Accessibility, Inclusion, and Diversity in Critical Event Studies - Finkel, Rebecca; Sharp, Briony; Sweeney, Majella; Taylor and Francis (Boca Raton, FL : Routledge Academic, 2018)
Most early social research into planned events had the effect of broadcasting narratives of dominant cultures and privileged groups. More recently, however, convergences of gender, sexualities, ethnicities, age, class, religion, and intersectional analyses and events studies have started to drive new critical understanding of the impacts of events on non-mainstream, non-majority communities around the globe. This timely book addresses current gaps in the literature surrounding issues of accessibility, inclusion, and diversity in various event landscapes. Structured into four parts covering the main types of events, the chapters present original topics using innovative methodological approaches. Each chapter employs a case study to illustrate the key intertwining issues in these various experiential realms. Further, the chapters are all cross- or interdisciplinary, drawing on gender, sexualities, cultural, race/ethnicity studies as well as multiple literatures that feed into critical events studies and exploring a variety of global examples. This significant book opens the path to further research on the role and importance of accessibility, inclusion, and diversity in events environments worldwide. It will be of interest to academics and researchers of critical event studies as well as a number of related social science disciplines.
Introduction -- --Rebecca Finkel, Briony Sharp, and Majella Sweeney -- PART I Festivals and fairs -- 1 Addressing community diversity: the role of the festival encounter -- --Michelle Duffy, Judith Mair, and Gordon Waitt -- 2 Inclusion of people with reduced mobility in festivals: perceptions and challenges at the Guelaguetza Festival, Mexico -- --Daniel Barrera-Fernndez and Marco Hernndez-Escampa -- 3 Do-it-yourself or going professionally?: on the different potentials of community inclusion through gendered festivals in the post-Yugoslav space -- --Zorica Siroi -- 4 Appleby Fair for all -- --Teresa Crew -- 5 Agricultural shows: the challenge of accessibility -- --Caroline A. Wiscombe -- PART II Cultural and political events -- 6 "House and techno broke them barriers down": exploring exclusion through diversity in Berlins electronic dance music nightclubs -- --Naomi Alice Rodgers -- 7 Occupying unapologetically: Friday Late: gal-dem radical trust and co-production at the Victoria and Albert Museum, London -- --Keisha Williams -- 8 In our own words: organising and experiencing exhibitions as Black women and women of colour in Scotland -- --Layla-Roxanne Hill and Francesca Sobande -- 9 Outside the comfort zone: intercultural events in suspicious times -- --Roaa Ali -- 10 Performing advocacy -- --Caroline Gausden -- 11 Conceptualising events of dissent: understanding the Lava Jato rally in So Paulo, 5 December 2016 -- --Ian R. Lamond -- PART III Sporting events -- 12 Rio 2016 Paralympics and accessibility: breaking barriers in urban mobility? -- --Silvestre Cirilo Dos Santos Neto, Ailton Fernando Santana De Oliveira, Vinicius Denardin Cardoso, and Marcelo De Castro Haiachi -- 13 Volunteering and wellbeing: case study of the Glasgow 2014 Commonwealth Games volunteer programmes -- --Briony Sharp -- 14 Post-humanist investigation into humanequine relations in event landscapes: case of the Rodeo -- --Paula Danby and Rebecca Finkel -- PART IV Conferences -- 15 Measuring accessibility in MICE venues: the case of the Euskalduna Conference Centre (Bilbao, Spain) -- --Ainara Rodrguez-Zulaica and Asuncin Fernndez-Villarn Ara -- 16 Academics in two places at once: (not) managing caring responsibilities at conferences -- --Emily F. Henderson -- 17 A tripartite approach to accessibility, diversity, and inclusion in academic conferences -- --Trudie Walters
Includes bibliographical references and index.
Also available in print format.
Keywords: accessibility at conferences; accessible events; BAME representation; caring and events; diversity and events; events of dissent; Intercultural events; inclusion and events; paralympics; rodeo; volunteering at events; women of colour in Scotland; Special events -- Social aspects; Special events -- Planning; Special events -- Management; Social integration; Electronic books